(untitled) (Journal-of-Ethiopian-Church-Studies/የኢትዮጵያ-ቤተ-ክርስቲያን-ጥናት-መጽሔት-Live, 2023)
Having religious leaders who write books is very significant in the Ethiopian Orthodox Tewahedo Church as it not only provides spiritual guidance but also serves to encourage the laity to contribute through their own writings. When religious fathers take the initiative to pen their teachings and insights, it sets an example for the belivers and other religious fathers, inspiring the faithful to explore societal, religious and cultural issues thereby sharing their perspectives, spiritual teachings and experiences. This act of encouragement fosters a culture of intellectual engagement, enabling the laity to amplify their voices, contribute to religious discourse, and enrich the spiritual traditions of the Church. In this regard, His Eminence Abunä Samu’el has done a commendable thing and contributed his share.